Association between preadmission low‐density lipoprotein cholesterol concentration and risk of large intracerebral hemorrhage: Results from the Kailuan study. Issue 12 (28th November 2022) - Li, Zhanying; Hui, Ying; Sha, Zhuang; Liu, Bailu; Wang, Chengbo; Yang, Feng; Zhang, Wenfei; Gao, Chuang; Jiang, Rongcai
Abstract: Background: To examine the association between low‐density lipoprotein cholesterol (LDL‐C) concentrations and the risk of a large hematoma volume after intracerebral hemorrhage (ICH). Methods: Patients from the Kailuan study (Tangshan, China) who were hospitalized with ICH during 2006 and 2020 were included in this study. The concentration of lipid concentrations, hematoma volume and other clinical characteristics were retrospectively collected and analyzed. Hematoma volumes were measured on the first available brain scan using the ABC/2 method. LDL‐C concentrations were obtained from the last physical examination before the occurrence of ICH. LDL‐C concentration was categorized into four groups in accordance with the quartiles. Logistic regression was used to assess the association between LDL‐C concentrations and the risk of a large hematoma volume of ≥30 ml. A generalized linear regression model was used to analyze the dose–response relationship between LDL‐C concentration and hematoma volume. Results: A total of 836 patients with ICH were evaluated. In the Multivariate logistic regression, compared to the second quartile of LDL_C, the first quartile of LDL_C had a significantly higher risk of a large hematoma volume (OR 2.49 [95% CI 1.54–4.01]), and the higher quartile of LDL_C is not associated with higher odds of large hematoma volume. In the generalized linear regression model, the adjusted β for the association between LDL‐C concentration and hematoma volume was 9.46 (95% confidence interval 2.87–16.04), whereas higher LDL‐C concentration was not associated with a large hematoma volume. Conclusions: This study confirmed that low LDL‐C concentrations prior to ICH are associated with a higher risk of a large hematoma volume. Abstract : The LDL_C concentrations were obtained from the last physical examination before the occurrence of ICH. The picture indicated that the patients with LDL‐C concentrations less than <1.95 mmol/L have a larger hematoma volume than the patients with LDL‐C concentrations less than 2.51 mmol/L and more than 1.95 mmol/L after intracerebral hemorrhage.